PENANAMAN NILAI-NILAI ISLAM MELALUI KESENIAN HADRAH - Farhan Ramadan (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2024)
History has explained that hadrah art has become an art that plays an important role in Islamic preaching. Hadrah art is performed at several religious events, such as weekly, monthly, and annual activities. This research aims to find out the important role of hadrah art in the city and regency of Bogor in helping convey Islamic preaching through qasidahs accompanied by hadrah art. The method used in this research is qualitative descriptive research. A method that collects data for research in observation, object observation, and documentation. The results of this research show that hadrah art can more easily attract listeners who attend together to read prayers and convey religious values. The implementation of this hadrah art calms the human mind and improves human morals through the chanting of the poetry values conveyed, so that it can raise enthusiasm for religious spirituality. This creates a positive value in a meeting to equip those present with religious values for everyday life because they hear knowledge about the struggle of the Prophet Muhammad, their obligations as Muslims, and religious advice.